Physical and sports education as a means of reducing school bullying behaviour - بن العربي, يحي (sports creativity, 2025)
مجلة االبداع الرياضي: ISSN2170-0818EISSN:5094-2602 املجلذسقم "(13" )/ العذدسقم " (01" )–2022/الصفحة:597-610 المؤلف المرسل :بن العربي يحي.البريد االلكتروني للمرسل :y.benlarbi@univ-djelfa.dz -جامعة محمد بوضياف حقوق النشر محفوظة لدى–المسيلة-.الموقع االلكتروني :https://www.asjp.cerist.dz/en/PresentationRevue/316 حصة التربية البذهية و الشياطيةكوظيلة للتقليل منظلوكالتنمشاملذسس ي Physical and sports education as a means of reducing school bullying behaviour بن العشبي ًحـي Benlarbi Yahia حامػت ش ٍان غاػىز–الجلفت ،y.benlarbi@univ-djelfa.dz ثاسيخالاظتالم:03/01/2022ثاسيخالقبول:06/04/2022ثاسيخالنشش:01/06/2022 امللخص : ٌ حػدد أوؼوتها، وجىىغها ئلى ئغداد الفسد ئغدادا مخيامال ومخىاشها بد ُث ً زال حػمل خـت الترب ُت البده ُت و الس ٍاك ُت م جصوده بمسخلف الخبراث، ئذ حػخبره الػامل الحاطم في ئغدادشخـُت الفسد، ومػسفت أبػادها م ً زال ٌ الاخخيان باألزسًٍ. ولهرا الغسق اهخمذ باغداد الخلمُر املساهم صحُا، هفظُا واحخماغُا . وكد طعى الباخث م ً زال ٌ هره املدزس ي. ولهرا الغسق اطخسدم ً الخىمس الدزاطت ئلى الخػسف غلى دوز خـت الترب ُت البده ُت والس ٍاك ُت في الخلل ُل ماملىهج الىؿفي غلى غُىت مخيىهت م ً (100) جلم ُر. جم ازخ ُازها بؼيل غؼىائي، ولجمؼ الب ُاهاث جم اطخسدام مل ُاض الخىمس املدزس ي، وبػد حمؼ الىخائج ومػالجتها ئخـائ ُا، جم الخىؿل الى أن خـت الترب ُت البده ُت والس ٍاك ُت لها دوز ا ًجابي في املدزس ي . ً الخىمس الخلل ُل م-الكلمات املفتاحية :خـت التربُت البدهُت و السٍاكُت،الخىمس املدزس ي. Abstract : The physical and sports education works through its many activities, its diversity to an integrated and balanced preparation of the individual, which provides him with various experiences, considering him to be the decisive factor in the preparation of one's personality and the knowledge of its dimensions through friction with others. To this end, it has taken care of the healthy, psychological and social preparation of the adolescent pupil. Through this study, the researcher sought to identify the role of physical and sports education in reducing school bullying. For this purpose, the descriptive method was used on a sample of 100 pupils. It was chosen randomly, data collection used as a measure of school bullying, and after the results were collected and dealt with statistically, the physical and sports education quota was found to play a positive role in reducing school bullying.